The Impact of Road Light on Growth and Result of Soybean Plant - Jajuk Herawati; I. Indarwati; Tatuk Tojibatus S.; Mochamad Thohiron; Heru Prasetyo (Universitas Sembilanbelas November Kolaka, 2020)
Until now, soybean is still one of the priority food commodities in Indonesia. in the agricultural revitalization program launched by the government in 2005, due to the high price volatility that did not rule out the possibility of shaking the Indonesian economy. Soybean plants can provide positive and negative responses to environmental changes growing above and in the soil. This response can be known from phenotypic and physiological changes in plants. The environment on land which influences the growth of soybean plants mainly is the duration and intensity of irradiation, air temperature, CO2 content in the atmosphere. The study aims to determine the impact of street lighting on the growth and yield of soybean plants. The study used a Randomized Block Design Method with 3 treatments, and each treatment was repeated 9 times, so that it takes 27 treatment plots. J0= Distance of street lighting to soybean land (meters), J1: 50 meters, J2: 60 meters, and J3: 70 meters. Observations were made one week after planting at 7-day intervals for growth parameters (plant height and number of leaves), while for the production parameters (Number of Content Pods/Plants, Dry Weight (DW) 100 Seeds, DW Seeds/Plots, and DW Seeds/Ha) are carried out after harvest. From the results of the study it can be concluded that there are real differences in the parameters of growth and production (number of filled pods, DW 100 seeds, DW seeds/plot, and DW seeds/ha), where the J3 treatment is capable of producing 2.89 tons/ha (an increase in dry weight of seeds/ha by 28.4%), compared to J1 2.24 tonnes/ha , although not significantly different from Treatment J2